Milgram's shock experiments and the Nazi perpetrators: A contrarian perspective on the role of obedience pressures during the Holocaust. (October 2015) - Fenigstein, Allan
In contrast to many scholars who believe that Milgram's studies of obedience provide an incisive understanding of the Holocaust perpetrators, this article argues that pressures to obey authority had little role in the Holocaust. Unlike Milgram's participants, most Nazi perpetrators showed no remorse or moral distress over the murders, severely compromising the explanatory necessity of obedience pressures; the excesses of the Nazis' brutal and wanton cruelty, and the enthusiasm shown in the killing process, is entirely inconsistent with the behavior of the laboratory participants and with the concept of dutiful, but emotionless, obedience; and finally, when Milgram's participants had the chance to evade giving shock, they frequently seized that opportunity; in contrast, although Nazi killers were often given the opportunity to withdraw from the killing operations, very few chose to do so. These arguments suggest that most of the Nazi perpetrators believed in what they were doing, and would have been willing, perhaps even eager to kill Jews, even in the absence of orders to do so.